Analysis of Genotoxic Damage in Different Diseases - Göney, Gülşen; Halisdemir, Nurhan (Necmettin Erbakan Üniversitesi, 2021)
Aim: Research has revealed that diseases changed the repair mechanism of DNA chain breaks. Recent studies indicate that genomic instability results in cancer. The present study aimed to assess the association between diseases and DNA damage measured with the comet assay in humans. Method: In a cross-sectional study the level of genotoxic damage was evaluated in peripheral blood samples by simple random sampling method in Turkish adults using Single Cell Gel Electrophoresis assay. The results of possible DNA damage levels of disease groups were compared with the results of healthy people. A p-value of less than 0.01 was considered as statistically significant. Results: 128 (52 women and 76 men) participated in the study. The tail moment was 1.39±1.21 in healthy groups and 1.41±0.91 in patient groups. Our result showed that participants with hepatitis, thyroid dysfunctions, and psychiatric diseases had statistically significant differences in DNA damage compared to healthy ones. Conclusion and Suggestions: Our findings suggest that patients with hepatitis, thyroid dysfunctions, and psychiatric diseases are at risk of genotoxic damage. Genotoxicity tests have gained importance in early biomonitoring of cancer. Therefore, the relationship between diseases and cancer development should be investigated with different genotoxic experiments.

Amaç: Son yıllarda yapılmış olan araştırmalar ile obezitenin, DNA zincir kırıklarının onarım mekanizmasını değiştirdiği ortaya çıkartılmıştır. Ayrıca Beden Kitle indeksinde artış ile genomik kararsızlık arasında ilişki tespit edilmiştir. Sunulan çalışmada farklı hastalık gruplarındaki bireylerde muhtemel genotoksik hasarının araştırılması amaçlanmıştır. Yöntem: Sunulan çalışmada 18 yaşından büyük aşırı kilolu ya da normal kiloya sahip bireylerin periferal lenfositlerinde olası DNA hasarı comet deneyi ile analiz edilmiştir. Farklı hastalık gruplarındaki kişilere ait olası DNA hasar düzeyi sonuçları kontrol grubunu oluşturan sağlıklı kişilerin sonuçları ile SPSS analiz programı kullanılarak istatistiksel olarak karşılaştırılmıştır. Bulgular: Sunulan araştırmaya yaş ortalaması 33,60±10,80 olan 52 kadın, 76 erkek 128 gönüllü katılmıştır. Sağlıklı bireylerden oluşan kontrol grubunda kuyruk momenti değeri 1.39±1.21 olarak tespit edilirken bu değer hastalığa sahip bireylerin oluşturduğu grupta 1.41±0.91 olarak tespit edilmiştir. Hastalık ve kontrol grubunda Kuyruk momenti değeri sonuçları karşılaştırıldığında tiroid ve hepatit hastalarında istatsitiksel oarak anlamlı fark bulunmuştıur (p
Farklı Hastalıklarda Genotoksik Hasarın Analizi
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi